Lapangan Golf & Klub Eksekutif - Apriani, Fifi; Angrini, Sisca Novia (Jurnal TekstuReka, 2024)
Humans have limitations in their ability to carry out activities, so when they reach boredom, they have to look for other activities to replace their current routine, looking for something that can make them happy and help them forget about tiring routine activities. Golf is a great sport, but it requires patience and calm. Therefore, more precision is needed in addition to strong strength. When making the first shot, golfers often use their strength to aim longer to get closer to the green or hole. Golf can be played at the driving range, which is a place where golfers can practice their skills, or on a golf course, which is more often called a driving range. Apart from sports venues, there are facilities for bringing people together with shared interests and meeting for enjoyment. This design uses contemporary architecture as its theme. It is hoped that the design approach that is presently "trending" or being created will be the background for selecting the design theme. whatever is happening at the moment. Modernity is more fluid and not bound by era.